Pemodelan Debit Banjir Rencana Berbasis Data Hujan Satelit pada Daerah Tangkapan Air Bendungan Meninting - Dionysius Edna Hartyan; Suripin Suripin (Department of Civil Engineering, Diponegoro University, 2024)
Rainfall stations around the Meninting Dam catchment area are very limited. Global Precipitation Measurement (GPM) satellite rainfall data can be utilized to fulfill the lack of rainfall data. This research aims to improve the quality of flood discharge in the Meninting Dam catchment area through rainfall data correction. GPM rainfall data was corrected using the probability curve method, while flood discharge analysis used HEC-HMS modeling. The results showed that the correlation coefficient of GPM rainfall data with Sesaot Rainfall Station was 0,73, the average HHMT error decreased by 2.99% after correction, and the correction factor level was 0-1,2 for each rainfall value range. The flood discharge (Q) of HEC-HMS modeling for each return period was obtained Q2th = 117,1 m3/sec, Q5th = 142,5 m3/sec, Q25th = 242,3 m3/sec, Q100th = 335,6 m3/sec, Q1000th = 529,3 m3/sec, and QPMF = 930,9 m3/sec.